Immunogenicity, efficacy and safety of the three-valent inactivated influenza split vaccine in patients with ankylosing spondylitis and psoriatic arthritis - M. M. Baranova; N. V. Muravyeva; B. S. Belov; M. E. Diatroptov (Научно-практическая ревматология, 2024)
According to the World Health Organization (WHO), worldwide, annual influenza epidemics lead to approximately 3–5 million cases of severe forms of the disease and 250–500 thousand deaths. The problem of the course and outcomes of influenza is also relevant for patients with immunoinflammatory rheumatic diseases, including spondyloarthritis (SpA). However, data on the immunogenicity, efficacy and safety of influenza vaccines in patients with SpA are limited.The aim of the work was to study the immunogenicity, efficacy and safety of the trivalent inactivated influenza split vaccine in patients with ankylosing spondylitis (AS) and psoriatic arthritis (PsA), observed at the V.A. Nasonova Research Institute of Rheumatology.Materials and methods. 94 people were included in the study: 28 patients with AS, 14 patients with PsA, 52 patients in control group (СG) without immunoinflammatory rheumatic diseases. Vaccination with a trivalent inactivated influenza split vaccine was carried out over three consecutive epidemic seasons: 2020–2021, 2021–2022, 2022–2023. The majority of patients (71,4%) received immunosuppressive therapy. The trivalent inactivated influenza split vaccine was administered in an amount of 1 dose (0.5 ml) intramuscularly against the background of anti-rheumatic therapy, regardless of the activity of the main IVR. The level of antibodies (AT) of class G to hemagglutinin (HA) of influenza A (H1N1), A (H3N2) and B viruses was determined using enzyme immunoassay systems manufactured by PPDP LLC (St. Petersburg, Russian Federation) before vaccination, 1–3 (on average, 1,6±0,8) and 6 months after it. The clinical efficacy and safety of trivalent inactivated influenza split vaccine were also evaluated, including the effect on the activity of AS and PsA according to the dynamics of BASDAI and DAPSA indices.Results. At the second and third visits after vaccination the level of AT, determined in units of optical density, to HA of influenza A (H1N1), A (H3N2) and B was significantly higher compared to baseline values. During follow-up, influenza or flu-like disease according to WHO criteria were absent in 37 patients. In general, there was no negative effect of vaccination on the activity of the underlying disease. The frequency of postvaccinal reactions in patients and in СG was comparable.Conclusions. The obtained results of the study indicate sufficient immunogenicity, clinical efficacy and safety of trivalent inactivated influenza split vaccine in patients with AS and PsA.